The Development of Electronic-Worksheets (E-Worksheets) Based on Crosswords Games with Sub-Materials of The Excretory System to Improve The Motivation of High School Students - Indiarti Dwi Fina; Raharjo Raharjo; Erlix Rakhmad Purnama (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2022)
Education in the 4.0 industrial revolution era has a curriculum that utilizes the internet of things (IoT) as a source or media in the learning process. Learning media that support is e-worksheet with crosswords games that will help students be motivated in the learning process. This study aims to develop a valid and practical e-worksheet based on crossword games with sub-materials Excretory System to improve learning motivation of students. This study is development research that uses the ASSURE model with steps: Analyze learners, State objectives, Select method, media, and materials, Utilize materials, Require learners’ performance and Evaluate/Revise. The e-worksheet research trial included 20 students of XI grades from Muhammadiyah 10 Gresik. Validity was determined by material experts, media experts, and a biology teacher at SMA Muhammadiyah 10 Gresik. The practicality of the e-worksheet was determined using students’ response questionnaire, students’ motivation questionnaire before and after using the product, implementation of motivation, and student activities. Validity and practicality data were analyzed using the descriptive quantitative. The result showed that the developed e-worksheet obtained an average validity percentage of 98.14% with very valid criteria. The practical e-worksheet obtained 93.5% of students’ responses, the increase in students’ motivation improvement from 60.1% to 86.8%, and 91.67% observation motivations implementation. The data that is received shows that e-worksheet based on crossword games are very valid and practical. Keywords: e-Worksheet, Crosswords, Excretory System, Motivation